Unraveling E-commerce and Retailing: Insights from Extensive Data Analysis - Wati, Anindya Pramitaqwati; Rosnawati, Emy; Rositasari, Dewi (Proceedings of The ICECRS, 2023)
This data article presents a comprehensive analysis conducted on Lens.org, focusing on documents related to E-commerce and Retailing. By employing keyword searches like "e-commerce AND Retailing," we retrieved a total of 19,091 documents. Subsequently, filtering for journal articles and conference proceedings resulted in 12,867 relevant documents. The study highlights key findings: London Queensland University of Technology stands out with 83 documents, while the peak scholarly output occurred in 2019 with 1,215 journal articles. Business emerged as the dominant field of study, encompassing 5,365 documents. Active institutions like University of Pennsylvania and Cardiff University explored Economics and Business, contributing significantly. Yogesh K Dwivedi emerged as the most prolific author, producing 45 documents. Notably, the study reveals a seminal work titled "Golden Eggs and Hyperbolic Discounting" in 1997, accumulating 4,964 accessible documents. The United States led in active contributions with 2,067 documents. Elsevier emerged as the top publisher, producing 2,076 documents, including the SSRN Electronic Journal. This dataset serves as a valuable resource for researchers delving into the intersection of E-commerce and Retailing, offering insights into trends, prolific authors, and institutional contributions. Highlights: Comprehensive E-commerce Research: A detailed analysis of 19,091 documents retrieved from Lens.org, shedding light on the dynamic landscape of E-commerce and Retailing studies. Prolific Institutions: London Queensland University of Technology leads with 83 documents, showcasing active academic engagement in this field. Scholarly Output Peaks: The year 2019 witnessed a surge with 1,215 journal articles, reflecting heightened research interest and productivity. Keywords: E-commerce, Retailing, Scholarly Publications, Academic Contributions, Business Trends